Raíces judeocristianas del liberalismo. Breve estudio sobre un antecedente remoto del constitucionalismo - Zamorano Aragón, Luis Eduardo (2023)
Constitutionalism is at present experiencing a severe crisis which consists of having forgotten its original sense and not being able to fulfil the purpose originally assigned to it. In trying to understand that crisis, we attempt a long historical detour in which an ancient Judaeo-Christian institution, that of divine sovereignty, will be studied. The aforementioned could show that the problem of constitutionalism is due to an error in the way in which the question about power is expressed, which would require that the question is re-stated and a new answer sought.